2019
DOI: 10.1021/acs.iecr.9b03627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu Precursor Types on the Catalytic Activity of Cu/ZrO2 toward Methanol Synthesis via CO2 Hydrogenation

Abstract: This paper presents the influence of different types of copper precursors on CO2-to-methanol hydrogenation over copper nanoparticles on amorphous ZrO2. Here, we chose copper nitrate hydrate, copper acetate hydrate, and a copper ammine complex as the precursor. A copper-acetate-based catalyst, which was precalcined at 350 °C, was more active and selective toward methanol than were the other catalysts. Regardless of the different copper precursors, after calcining a mixture of a copper precursor and amorphous Zr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 80 publications
4
33
0
Order By: Relevance
“…The methanol yield of CZ (9 mmol h -1 g-Cu -1 ) was higher than that of MDC (7 mmol h -1 g-Cu -1 ), and the methanol selectivity of CZ (64.0 %) was higher than that of MDC (29.6 %). Therefore, CZ catalyst was more specific for CO2-to-methanol hydrogenation than MDC, consistent with our previous report 27) . The formation rates of CH3OH and DME over CZ FER (6 mmol h -1 g-Cu -1 ) were approximately three-fold higher than those over MDC FER (2 mmol h -1 g-Cu -1 ) despite the same F/W (ca.…”
Section: Comparison With Cu-zn Catalystsupporting
confidence: 92%
See 3 more Smart Citations
“…The methanol yield of CZ (9 mmol h -1 g-Cu -1 ) was higher than that of MDC (7 mmol h -1 g-Cu -1 ), and the methanol selectivity of CZ (64.0 %) was higher than that of MDC (29.6 %). Therefore, CZ catalyst was more specific for CO2-to-methanol hydrogenation than MDC, consistent with our previous report 27) . The formation rates of CH3OH and DME over CZ FER (6 mmol h -1 g-Cu -1 ) were approximately three-fold higher than those over MDC FER (2 mmol h -1 g-Cu -1 ) despite the same F/W (ca.…”
Section: Comparison With Cu-zn Catalystsupporting
confidence: 92%
“…The gel was dried at 110 °C overnight and calcined at 350 °C for 5 h in an elec-tric furnace. According to our previous research 25) 27) , copper cations in the catalyst were doped into the amorphous ZrO2. Cu/ZnO/Al2O3 (MDC-7 supplied by Clariant K.K.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the complexes built from Cu cations and oxygen vacancies preferentially on t-ZrO 2 were proposed as the active site for the methanol synthesis reaction. Tada et al (2019) demonstrated the importance of the interfacial area and surface basicity on the catalytic activity for Cu/ZrO 2 catalysts. Utilizing a Cu nitrate precursor resulted in residual nitrogen that bound to basic sites of the ZrO 2 support, which reduced the activity of the catalysts.…”
Section: Effect Of Other Metal Oxide Components On Cu-based Catalystsmentioning
confidence: 97%